Language Competences for Effective Teaching Practice - Pererva, Kateryna M.; Afanasieva, Larysa V. (Херсонський державний університет, Херсон, 2018)
EN: The aim of this article is to show the importance of language competences forming in the classroom in order to get a perfect acquisition of the second language. This paper examines what competencies a learner of English as a Foreign Language (EFL) can develop while developing communicative competence in English. Also this paper deals with some activities that develop those skills and shows why it is important to boost those qualifications.

EN: The aim of this article is to show the importance of language competences forming in the classroom in order to get a perfect acquisition of the second language. This paper examines what competencies a learner of English as a Foreign Language (EFL) can develop while developing communicative competence in English. Also this paper deals with some activities that develop those skills and shows why it is important to boost those qualifications.

UK: Метою даної статті є висвітлення важливості формування іншомовних компетенцій студентів на заняттях англійської мови. У статті встановлено, які саме компетенції може розвинути студент, що вивчає англійську мову як іноземну, під час розвитку комунікативної компетенції з англійської мови. Також у статті розглянуто деякі види діяльності та вправ, що можуть бути використаними для розвитку даної компетенції.

RU: Целью данной статьи является освещение необходимости формирования языковых компетенций студентов на занятиях английского языка. В статье установлено, какие именно компетенции может развить студент, изучающий английский язык как иностранный, при развитии коммуникативной компетенции по английскому языку. Также в статье рассмотрены некоторые виды деятельности и упражнений, которые могут быть использованы для развития данной компетенции.
Мовні компетенції для ефективного викладання
Языковые компетенции для эффективного преподавания
K. Pererva: ORCID 0000-0002-9154-9407; L. Afanasieva: ORCID 0000-0002-5051-8700
Keywords: speaking; reading; competence; importance; development; difficulties; activities; teaching and learning; говоріння; читання; компетенція; розвиток; складнощі; завдання; викладання; навчання; говорение; чтение; компетенция; важность; развитие; сложности; задания; преподавание; обучение; КІМ